Who merits more concern: university teachers under task-related or those under interpersonal-related stress? - Mei Tian; Xiaoyue Li; Junchi Ma; Tong Zhang; Peng Wang; Xiqing Yuan; Xiao Wang (Humanities & Social Sciences Communications)
Abstract The present study aims to explore group types of job stress in university teachers in China. Utilizing an indigenously developed university teachers’ job stress scale in China alongside other tools, a survey was conducted on 1988 teachers from 22 Chinese higher education institutions from a person-oriented perspective. Stratified cluster random sampling and K-means clustering techniques were employed to derive a classification model for job stress among university educators. According to job stress characteristics, Chinese university teachers were classified into six significantly heterogeneous groups: relatively high stress, task-related stress, relatively low stress, interpersonal-related stress, extremely low stress, and extremely high stress. The average job burnout and job satisfaction scores of the different groups exhibited varying features. In general, the extremely high stress group should be the most concerned, whereas university teachers with mid-level stress merit less attention. But the medium-stress group was further subdivided. University teachers under task-related stress have more stress-related consequences than those of university teachers under interpersonal-related stress. There are significant differences in the distribution of university teachers’ job stress group types across demographic groups defined by gender and university types. University administrators should focus on university teachers under task-related stress. This classification model offers direct references for the stress management and psychological aid of university teachers.